2009
DOI: 10.1002/jbm.b.31498
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity evaluation of biodegradable and thermosensitive PEG‐PCL‐PEG hydrogel as a potential in situ sustained ophthalmic drug delivery system

Abstract: In this work, a biodegradable poly(ethylene glycol)-poly(epsilon-caprolactone)-poly (ethylene glycol) (PEG-PCL-PEG, PECE) triblock copolymer was successfully synthesized, which was flowing sol at low temperature and turned to nonflowing gel at body temperature. The toxicity evaluation of PECE hydrogel as a potential in situ sustained opthalmic drug delivery system was performed, including the biodegradability of PECE hydrogel in the eye, its effect on cultured human lens epithelia, intraocular pressure, and oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 26 publications
(40 reference statements)
4
23
0
5
Order By: Relevance
“…The injectable PECE hydrogel is thermosensitive nano-material which is flowing sol at low temperature that turns to nonflowing gel at body temperature. Our previous studies have shown its safety to be intracamerally injected as an ideal sustained ophthalmic drug delivery system [14,15]. So, in the current study, we provide data that the antifibrotic effect of bevacizumab loaded PECE hydrogel intracameral injection is superior to bavacizumab alone in the management of postoperative scarring after GFS in the rabbits.…”
Section: Introductionsupporting
confidence: 51%
“…The injectable PECE hydrogel is thermosensitive nano-material which is flowing sol at low temperature that turns to nonflowing gel at body temperature. Our previous studies have shown its safety to be intracamerally injected as an ideal sustained ophthalmic drug delivery system [14,15]. So, in the current study, we provide data that the antifibrotic effect of bevacizumab loaded PECE hydrogel intracameral injection is superior to bavacizumab alone in the management of postoperative scarring after GFS in the rabbits.…”
Section: Introductionsupporting
confidence: 51%
“…This hydrogel system showed good biodegradability, sustained release, and ocular biocompatibility, indicating that the system is a safe candidate for sustained ophthalmic drug delivery. Many other in situ polymeric gelling systems, such as chitosan, 80 poloxamer, 81 HPMC, 82 PEG-poly-e caprolactone (PCL)-PEG, 83 poly(N-isopropylacrylamide)/chitosan, 84 poloxamer/ chitosan, 85 pluronic F-127/chitosan, 86 and poloxamer/ carbopol 87 were explored for topical ocular applications.…”
Section: Pluronicsmentioning
confidence: 99%
“…Data indicated that the prepared hydrogel was biocompatible and biodegradable despite the temporary elevated intraocular pressure and slight corneal endothelial damage at specific concentrations. Therefore, this hydrogel showed great biocompatibility, biodegradability, and sustained release property in eyes, making this system a safe candidate for sustained ophthalmic drug delivery [105]. Furthermore, Gong et al [106] studied a PEG-PCL-PEG hydrogel system for basic fibroblastic growth factor (bFGF) antigen delivery.…”
Section: Pharmaceutical Applicationmentioning
confidence: 99%